Little women (1933) [videorecording (DVD)] - Cukor, George, 1899-1983; Hepburn, Katharine, 1907-2003; Bennett, Joan, 1910-1990; Lukas, Paul, 1894-1971; Oliver, Edna May, 1883-1942; Parker, Jean; Dee, Frances, 1907-2004; Alcott, Louisa May, 1832-1888 (Warner Home Video, 2001)
Chronicles the humorous and sentimental fortunes of the four March sisters as they grew into young ladies during the harsh times of the Civil war.